PENGARUH ALIRAN MODAL, SISTEM KEUANGAN, INFLASI, DAN PARTISIPASI TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI 12 NEGARA KAWASAN ASIA PASIFIK PADA TAHUN 2009-2019 - Azzaky, Hadika Raihan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of capital flow, financial system, inflation, and labour participation on economic growth in twelve countries asia pacific region. This research is quantitative research with liner regression methods which data collected through the World Bank website. The collected data were processed and tested through the classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test) and hypothesis testing with linear regression analysis and the coefficient of determination. The test in this research used a econometrics application program program, STATA version 16. The results showed that the inflation level (X5) partially have a negative and insignificant effect on economic growth (Y), meanwhile foreign direct investment (X1); stock capitalization (X2); domestic loans bank financial institutions (X3); domestic loans non bank financial institutions and labour participations (X5) partially have a positive and significant effect on economic growth (Y). From the results of simultaneous statistical testing, it was found that the foreign direct investment (X1); stock capitalization (X2); domestic loans bank financial institutions (X3); domestic loans non bank financial institutions and labour participations (X5) simultaneously have a significant effect on economic growth (Y) by 77.72% while the remaining 22.28% is affected by other variables outside the model adopted in this study.